2020
DOI: 10.1002/ece3.6008
|View full text |Cite
|
Sign up to set email alerts
|

The uplift of the Qinghai–Tibet Plateau and glacial oscillations triggered the diversification of Tetraogallus (Galliformes, Phasianidae)

Abstract: The Qinghai–Tibet Plateau (QTP) plays an important role in avian diversification. To reveal the relationship between the QTP uplift and avian diversification since the Late Cenozoic, here, we analyzed the phylogenetic relationship and biogeographical pattern of the genus Tetraogallus (Galliformes, Phasianidae) and the probable factors of speciation in the period of the QTP uplift inferred from concatenated data of four nuclear and five mitochondrial genes using the method of the Bayesian inference. Phylogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(53 citation statements)
references
References 70 publications
(121 reference statements)
0
53
0
Order By: Relevance
“…It is widely believed that the range of a large proportion of alpine species contracted under glacial oscillations, and that this phenomenon accelerated the process of genetic divergence. This premise has been documented in many species of plants [ 16 , 19 , 39 , 48 , 49 ] and animals [ 50 , 51 , 52 ]. Two bioclimate factors, ‘precipitation’ and ‘temperature’, were greatly reduced during the LGM [ 53 ], and have been identified as the major factors determining suitable distribution ranges for N. tangutorum ( Supplementary Table S4 ).…”
Section: Discussionmentioning
confidence: 86%
“…It is widely believed that the range of a large proportion of alpine species contracted under glacial oscillations, and that this phenomenon accelerated the process of genetic divergence. This premise has been documented in many species of plants [ 16 , 19 , 39 , 48 , 49 ] and animals [ 50 , 51 , 52 ]. Two bioclimate factors, ‘precipitation’ and ‘temperature’, were greatly reduced during the LGM [ 53 ], and have been identified as the major factors determining suitable distribution ranges for N. tangutorum ( Supplementary Table S4 ).…”
Section: Discussionmentioning
confidence: 86%
“…In a recent paper on the diversification of Tetraogallus snowcocks (Galliformes, Phasianidae), Ding et al ( 2020 ) reported on the discovery of three putative hybrid individuals that they supposed to have originated from a hybridization event between the Himalayan snowcock ( T . himalayensis ) and the Tibetan snowcock ( T .…”
Section: Introductionmentioning
confidence: 99%
“…himalayensis based on their phenotype. However, in Ding et al’s ( 2020 ) re‐analysis of the D‐loop data set by Wang et al ( 2011 ), the two crucial T . himalayensis sequences (H35 and H36) clustered with T .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations